Effects of nitrogen doping from pyrolyzed ionic liquid in carbon nanotube fibers: enhanced mechanical and electrical properties - Park, Ok-Kyung; Kim, Hwa Jung; Hwang, Jun Yeon; Kim, Seung Min; Jeong, Youngjin; Lee, Jae Kwan; Ku, Bon-Cheol (IOP PUBLISHING LTD, 2015)
Nitrogen doping in carbon nanotube (CNT) fibers using pyrolyzed ionic liquid induced interfacial hydrogen bonding between individual CNTs, enhancing mechanical properties and electrical conductivity simultaneously. In particular, the nitrogen doped CNT fiber using the ionic liquid BMI-I exhibited about 104%, 714%, and 38% increased tensile strength (0.65 N/ tex), elastic modulus (83 N/tex), and electrical conductivity (1350 S cm(-1)), respectively, compared to pristine CNT fiber.
Keywords: DOPED GRAPHENE; NANOCOMPOSITES; CONDUCTIVITY; CATALYST; YARNS